Attitude and Propensity to Divorce in Iran: Structural and Ideational Determinants. Issue 6 (18th August 2019) - Sadeghi, Rasoul; Agadjanian, Victor
ABSTRACT: Divorce has been increasing worldwide, even in societies where religious impediments to it are strongest. In the Islamic Republic of Iran, divorce rates have risen rapidly since the mid-1990s. In this article, we investigate the attitude and propensity of young Iranians toward divorce and relate these attitudes and propensities to structural and ideational factors. The data are drawn from a survey of 720 married people ages 15 to 29 conducted in the city of Tehran in 2014. The results show that almost half of respondents approved of divorce as a solution for marital problems and one fifth of them have high propensity to divorce. Multivariate analyses indicate that approval of and high propensity toward divorce are significantly associated with ideational factors—namely individualism, secularism, and gender egalitarian views—and structural factors—including education, wife's employment, and household economic insecurity—even after controlling for demographic variables. We discuss the implications of these findings for the understanding of marital stability in this rapidly changing context.